Interpretation of The Legal Values and Justice in The Living Law Related To Court Decision - Ismail Rumadan (Sociological Jurisprudence Journal, 2021)
The performance of judges in deciding on a legal dispute that is faced is a work process looking for legal norms both in the legislation and legal norms that live in the community. Based on the results of the above studies it can be concluded that; at the practical level there are two approach models used by judges to examine and adjudicate a civil case related to the values and rules of customary law in society, namely an evolutionist approach which holds the view that indigenous peoples are a community with barriers in the process of integration into the modern world, so that this transition process must be guarded through legal procedures. This view has an effect on the pattern of approaches used in dealing with a case related to customary issues and norms living in the community, this approach in view of the formalistic legal approach influenced by the possibility of legism-positivism, so that in some cases the disputed adat the right to customary land in Papu the judge always put forward formal proof of ownership of letters explaining proof of ownership of a plot of land, so that many customary civil cases must be rejected by the Court because the Plaintiff or the defendant can not prove formally proof of ownership over the disputed land.